Potential prescribing omissions of anti‐osteoporosis drugs is associated with rehabilitation outcomes after fragility fracture: Retrospective cohort study. Issue 5 (28th February 2021) - Shibasaki, Koji; Asahi, Toshiomi; Kuribayashi, Mari; Tajima, Yuriko; Marubayashi, Miki; Iwama, Risa; Akishita, Masahiro; Ogawa, Sumito
Abstract : Aim: We investigated the association between rehabilitation outcomes and polypharmacy, potentially inappropriate medications and potential prescribing omissions in older adults with fragility fractures. Methods: In total, we registered 217 older adults with fragility fractures (hip or vertebral) retrospectively and examined the association between rehabilitation outcome and polypharmacy, potentially inappropriate medications and potential prescribing omissions. Polypharmacy was defined as five or more drugs. Potentially inappropriate medications and potential prescribing omissions were defined by the Beers criteria (2015) and the screening tool to alert to treatment criteria version 2, respectively. The outcome was functional independence measure gain (functional independence measure at discharge – functional independence measure at admission). Results: Multiple regression analyses revealed no association between functional independence measure gain and polypharmacy (crude: β = 0.058, P = 0.858; adjusted model: β = 0.013, P = 0.869) or potentially inappropriate medications (crude: β = 0.100, P = 0.144; adjusted model: β = 0.084, P = 0.260). However, there was a significant association between functional independence measure gain and potential prescribing omissions (crude: β = 0.167, P = 0.014; adjusted model: β = 0.180, P = 0.016). Participants without potential prescribing omissions (in other words, participants who were prescribed anti‐osteoporosis drugs) had a greater functional independence measure gain than participants with potential prescribing omissions (in other words, those that were not prescribed anti‐osteoporosis drugs). Conclusion: To the best of our knowledge, this study is the first to report that participants without potential prescribing omissions had significantly improved rehabilitation outcomes. Geriatr Gerontol Int 2021; 21: 386–391 .